Evaluation of Focal Hepatic Lesion and associated changes in Gallbladder and Kidneys using Spiral Computed Tomography: Focal Hepatic Lesion in Gallbladder and Kidneys - Faazal, Ayesha; Sana, Sadia; Huraira, Abu; Fatima, Noor; Sana, Somara; Siddique, Zafaar (Pakistan Journal of Health Sciences, 2022)
Focal hepatic lesions are the lesions in the liver apart from its usual parenchyma. Objective: To check the efficiency of triphasic computed tomography for diagnosing benign and malignant focal liver lesions and to assess frequencies of both types of liver lesions. Methods: On 60 patients, triphasic CT scan for the liver was performed in Allied Hospital, Faisalabad. The liver was scanned in the arterial, the portal-venous, and the delayed phases followed by contrast injection. During all of these phases evaluation of lesions was made on enhancement patterns and frequencies of each lesion was checked. Results: The results showed that out of 60 patients 26(43.3%) were diagnosed with benign and 34(56.67%) were diagnosed with malignant focal liver lesions. Benign cases had a higher frequency of Haemangioma and malignant cases had a higher frequency of hepatocellular carcinoma. The overall study showed the percentage of incidents in gallbladder and renal system. Conclusions: The triphasic CT liver due to its accuracy provides assured diagnosis for liver lesions and thus reduces biopsy procedures